Dynamics of thermographic skin temperature response during squat exercise at two different speeds. (July 2016) - Formenti, Damiano; Ludwig, Nicola; Trecroci, Athos; Gargano, Marco; Michielon, Giovanni; Caumo, Andrea; Alberti, Giampietro
Abstract: Low intensity resistance training with slow movement and tonic force generation has been shown to create blood flow restriction within muscles that may affect thermoregulation through the skin. We aimed to investigate the influence of two speeds of exercise execution on skin temperature dynamics using infrared thermography. Thirteen active males performed randomly two sessions of squat exercise (normal speed, 1 s eccentric/1 s concentric phase, 1 s; slow speed, 5 s eccentric/5 s concentric phase, 5 s), using ~50% of 1 maximal repetition. Thermal images of ST above muscles quadriceps were recorded at a rate of 0.05 Hz before the exercise (to determine basal ST) and for 480 s following the initiation of the exercise (to determine the nonsteady-state time course of ST). Results showed that ST changed more slowly during the 5 s exercise ( p =0.002), whereas the delta (with respect to basal) excursions were similar for the two exercises ( p >0.05). In summary, our data provided a detailed nonsteady-state portrait of ST changes following squat exercises executed at two different speeds. These results lay the basis for further investigations entailing the joint use of infrared thermography and Doppler flowmetry to study the events taking place both at the skin and the muscle level during exercises executed at slow speed. Highlights: Two speeds of exercise execution on skin temperature dynamics were studied. The skin temperature dynamics were different in the two exercises. Skin temperature changed more slowly in the exercise with slow speed. Similar temperature excursions were found in the two exercises.